Multi-body Dynamics Modeling and Analysis of Transmission Gear Rattle - Li Di; Wu Guangqiang; Wu Huwei (Jixie chuandong)
The transmission gear rattle noise as a common noise of the mechanical transmission,which occurred on the meshing and unloaded gears,is mainly induced by the fluctuation of the engine output torque and the backlash gap. The generated mechanism of rattle is studied based on the impact,the multi- body dynamic equations of a pair of gear rattle is established,and the influence of rigid collision and elastic collision on gear rattle is analyzed and compared. To analysis the input speed and gear selection on transmission rattle,a multi- body dynamics model of gear system for a mechanical transmission is built by CATIA and ADAMS.